The Role of Modern Marital Therapies: A Comparative Analysis of the Effectiveness of the Gottman Approach and Cognitive-Behavioral Therapy on Marital Satisfaction (A Case Study of Married Students at Islamic Azad University, Hamedan Branch) - Saravi, Abdolreza; jadidyan, Ahmad Ali; Nejatian Tanha, Arezo (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to compare the effectiveness of Gottman couple therapy and cognitive-behavioral couple therapy in improving marital satisfaction among married students at Islamic Azad University, Hamedan Branch. Methods: The study utilized a quasi-experimental pretest-posttest design with a control group. A total of 45 married students were selected through convenience sampling and randomly assigned into three groups: Gottman couple therapy (n = 15), cognitive-behavioral couple therapy (n = 15), and a control group (n = 15). The intervention groups received 10 sessions of Gottman couple therapy or 8 sessions of cognitive-behavioral couple therapy, while the control group received no intervention. The ENRICH Marital Satisfaction Questionnaire (47-item short form) was used to assess marital satisfaction before and after the interventions. Data were analyzed using SPSS-24 software, employing multivariate analysis of covariance (MANCOVA) and one-way analysis of variance (ANOVA) to compare the effects of the interventions. Findings: The results indicated that both Gottman couple therapy and cognitive-behavioral couple therapy significantly improved marital satisfaction compared to the control group (p < 0.05). The effect size analysis revealed that Gottman couple therapy had a greater impact (η² = 0.789) compared to cognitive-behavioral couple therapy (η² = 0.721), particularly in areas related to emotional communication, conflict management, and decision-making. However, the ANOVA results showed no statistically significant difference between the two intervention groups (p > 0.05), indicating that both approaches were similarly effective in enhancing marital satisfaction. Conclusion: Both Gottman couple therapy and cognitive-behavioral couple therapy were effective in increasing marital satisfaction among married students, with Gottman couple therapy demonstrating a slightly greater impact. Given the shared principles of these approaches, future research should explore the potential benefits of integrating them to create a more comprehensive intervention for couples.